Prevalence of High-Intensity Drinking from Adolescence through Young Adulthood: National Data from 2016-2017. (January 2019) - Patrick, Megan E; Terry-McElrath, Yvonne M
High-intensity drinking (HID; ie, having 10+ drinks in a row) is a recognized public health concern due to the individual and public risks (eg, alcohol-related injuries, alcohol poisoning, memory loss, sexual risk) associated with consumption of a large quantity of alcohol over a relatively short time period. Using nationally representative samples of US 8th, 10th, and 12th grade students, and follow-up of subsamples of 12th graders, we present overall and sex-specific prevalence estimates of past 2-week HID from 29 966 individuals at the modal ages of 14 to 30 in 2016-2017. Similar data for the more commonly studied measure of binge drinking (having 5+ drinks in a row) is provided for comparison. HID prevalence ranged from 1% to 11.5% and was significantly higher for males than females at all ages other than modal age 14 (8th grade). Binge drinking prevalence ranged from 3.5% to 32.5%; males reported a higher prevalence than females at approximately half of the ages examined. Peak binge drinking and HID age for males was earlier (modal age 21/22) than that for females (modal age 21-24 for binge drinking and 25/26 for HID). The observed rapid increase in HID from adolescence through the early to mid-20s highlights the importance of prevention and intervention efforts targeted to these ages.